2009
DOI: 10.1016/j.juro.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Perianal-Intrarectal Lidocaine-Prilocaine Cream and Periprostatic Nerve Block for Pain Control During Transrectal Ultrasound Guided Prostate Biopsy: A Randomized, Controlled Trial

Abstract: Our findings suggest that the combination of perianal-intrarectal lidocaine-prilocaine cream and periprostatic nerve block provides better pain control than the 2 modalities alone during the sampling part of transrectal ultrasound guided prostate biopsy with no increase in the complication rate. The magnitude of this effect is higher in younger men, men with a larger prostate and men with lower anorectal compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 22 publications
1
94
2
1
Order By: Relevance
“…VAS pain scores were higher in patients with a small prostate and the difference was statistically significant in our study on the contrary to result of Giannarini et al and Yun et al 16,23 There may be more pressure to neurovascular bundle due to large size of prostate then some decrease may occure in transmission of pain percaption in those patient with large prostate. According to recent reports, higher prostate volumes do not necessarily increase the pain associated with the procedure.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…VAS pain scores were higher in patients with a small prostate and the difference was statistically significant in our study on the contrary to result of Giannarini et al and Yun et al 16,23 There may be more pressure to neurovascular bundle due to large size of prostate then some decrease may occure in transmission of pain percaption in those patient with large prostate. According to recent reports, higher prostate volumes do not necessarily increase the pain associated with the procedure.…”
Section: Discussioncontrasting
confidence: 98%
“…15 We also use combined anaesthesia which is suggested by Giannarini in our routine prostate biopsy procedures. 16 We believe in that administering perianal-intrarectal lidocaine cream before probe insertion decreases pain perception related to probe.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Giannarini et al found that the combination of perianal-intrarectal lidocaine-prilocaine cream and PPNB was able to provide better pain control than the two modalities alone, with no increase in the complication rate. The magnitude of this effect was higher in younger men, especially if with an enlarged prostate and lower anorectal compliance 44 .A recent meta-analysis confirmed that the combination of local analgesia and PPNB significantly reduced pain associated with probe manipulation, anesthesia, infiltration and needle biopsy. Subgroup analyses suggest that lidocaine-prilocaine cream proved the most effective pain control regardless of the origin of pain 38 .…”
Section: Painmentioning
confidence: 93%
“…These results suggest that a large dose of lidocaine-prilocaine (5g) intrarectal application 30 minutes prior to the procedure itself can achieve certain anesthetic effect on not only the procto canal but also the prostate gland. 63 …”
Section: Combination Peri-prostatic Block and Intra-rectal Local Anesmentioning
confidence: 99%
“…17,20,69,70 No significant complication differences were found with intraprostatic analgesia injection 64,67,68 or topical agents. 22,63,71 Of note, reported morbidity is confounded by the fact that many of the complications (i.e. bleeding, infection) can result from the prostatic biopsy itself (i.e.…”
Section: Complicationsmentioning
confidence: 99%